(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article is an overview of the concept of «private language». During the consideration is determined by the characteristics of the concept of «private language» as a cognitive phenomenon. In the study used a comparative methodological analysis. The notion of private language was considered in two ways, as a special form of language structures, or related to feeling like its referent. The study found that the concept of «private language» is a philosophical abstraction, re-created in a thought experiment. It is not possible to complete a communicative medium. This indicates justify logical arguments presented in this paper.